In situ conversion monitoring of styrene emulsion polymerization by deconvolution of a single reference band near 1, 000 cm−1. (10th September 2019) - Dropsit, E.; Hoppe, S.; Chapron, D.; Durand, A.; Bourson, P.
Abstract: Styrene emulsion polymerization was performed in batch reactor using Raman spectroscopy for in situ monitoring of styrene conversion. The variation of the band of trigonal aromatic ring breathing at 1, 000 cm −1 was analyzed in detail as a function of monomer conversion (wavenumber, integrated intensity, and half‐width at half‐maximum). The observed variation was described both qualitatively and quantitatively by a model assuming that the overall signal resulted from the addition of two close and distinct Gaussian signals, one originating from the monomer and the other one from the polymer repeat units. A reliable estimation of monomer conversion was obtained using the relative contributions of both components. The results were comparable to those obtained using the ratio of integrated intensities of the band at 1, 000 cm −1 (overlapping signals of monomer and polymer) and the band at 1, 631 cm −1 (signal specific to monomer). It was shown experimentally that information about monomer conversion could be obtained by applying linear model mixture to a single band of Raman spectrum, which provided an alternative method to the use of a ratio of integrated intensities. Abstract : In situ monitoring of styrene emulsion polymerization was performed using Raman spectroscopy. A reliable estimation of monomer conversion was obtained through a new analysis of the variation of the characteristics (wavenumber, integrated intensity, and half‐with at half‐maximum) of the band of trigonal aromatic ring breathing at 1000 cm ‐1 instead of using a ratio of integrated intensities as usually performed.